The Global Financial Crisis and Its Impact on Arab Financial Markets: An Analytical Study in Selected Arab Countries for the Period (2005-2010) - Abdulhussain Jasim Al-Asadi (Iraqi Journal for Administrative Sciences, 2025)
Global financial crisis is the subject of important topics in recent times as a result of its recurrence in the capitalist and developing countries , and this crisis is one of the most serious crises and came with negative effects on the global economy. Thus the study began with the premise that (no influence of global financial crisis on securities market indicators in sample) .The study aimed to identify financial crises and detect the causes of the current financial crisis (2008) as well as learn about the reality of Arab capital markets and identify the impact of this crisis on Arabic financial markets of the countries selected sample The study have reached several conclusions including that all the Arab stock market indices effected in (2006) as shown by these indicators meet most of the negative growth rates in that year demonstrating that the roots of this crisis were being found befor year (2006). The study found several recommendations, notably strengthening the possibility of developing a joint Arab action in building an integrated system of checks and surveillance organizations contributing to the advancement of the status of supervision and internal and external control of financial and banking sector in Arab countries.